The seismogenic source of the 2018 December 26th earthquake (Mt. Etna, Italy): A shear zone in the unstable eastern flank of the volcano. (January 2021) - Monaco, Carmelo; Barreca, Giovanni; Bella, Domenico; Brighenti, Fabio; Bruno, Valentina; Carnemolla, Francesco; De Guidi, Giorgio; Mattia, Mario; Menichetti, Marco; Roccheggiani, Matteo; Scarfì, Luciano
Abstract: The 2018 December 26th earthquake (MW = 4.9) at the south-eastern slope of Mt. Etna provides new insights for improving the knowledge of the kinematics of the eastern flank of the volcano. The earthquake was preceded by a seismic swarm on the upper southern-western sector of the volcano and by a short eruptive event in the summit area. The associated crustal deformation triggered seismic reactivation of tectonic structures in the eastern flank of the volcano. The seismogenic source has been localized along one of the segments cutting the south-eastern slope the volcanic edifice, the NW-SE trending Fiandaca Fault, one of the most active shear zone belonging to the upslope extension of the Timpe fault system. In the last centuries, all these faults have been the source of very shallow, low magnitude, but destructive earthquakes. In order to determine the response of the unstable eastern flank of Mt. Etna to the volcano-tectonic events, we applied a multidisciplinary approach based on: i) analysis of historical and instrumental seismicity; ii) mapping of coseismic fracturing, iii) analysis of GPS and InSAR data. This study allows to better define the seismotectonic framework of the shear zone occurring in the eastern flank of Mt. Etna, framing it in the seismogenic belt extending as far as the Ionian offshore.